TEACHING METHODOLOGY: MODERN APPROACHES TO EFFECTIVE EDUCATION - Zoxidova Muyassar (TADQIQOTLAR, 2025)
Teaching methodology plays a crucial role in improving the quality of education and ensuring that learners achieve meaningful results. Modern educational approaches emphasize student-centered learning, active participation, and the integration of technology. This paper discusses the key principles, methods, and benefits of contemporary teaching methodologies, highlighting their importance for both teachers and students.